Validation of the French Version of the Positivity Scale (P Scale) - Vancappel, Alexis; Courtois, Robert; Siragusa, Marta; Hingray, Coraline; Réveillère, Christian; Caprara, Gianvittorio; Belzung, Catherine; El-Hage, Wissam (Frontiers in Psychology, 2022)
Background The purpose of this study is to assess the psychometric properties of the French version of the Positivity scale (P scale), a self-report measure of positivity, which is the tendency to view and address life and experience with a positive outlook. Positivity is seen as a latent factor underlying multiple cognitive concepts such as self-esteem, life satisfaction, and optimism. Methods We recruited 666 volunteers (540 women and 126 men). They completed the P scale online, as well as self-report measures of psychological well-being, self-esteem, satisfaction with life, general health, and personality dimensions. The study sample was randomly split into two sub-groups, one used for exploratory factor analysis and the other for confirmatory factor analysis. Results We found conflictual results related to the uni-dimensionality of the French version of the P scale. We found good internal consistency and high concurrent validity. Conclusion The French version of the P scale demonstrated good psychometric qualities and is a reliable tool that can now be used by French researchers and clinicians to assess positivity.